Improving Direct Secure Messaging through Directory Management - Feterik, Kristian; Lusk, Katherine; Wickenhauser, Kathryn Ayers; McCormack, James L.; Lehmann, Christoph U.; Arvisais-Anhalt, Simone (Applied Clinical Informatics, 2025)
Direct Secure Messaging (DSM) is a communication standard for exchanging information between health care entities and practitioners. It relies on access to an address directory. When directory entry is incomplete, health information exchange breaks down. There is an urgent need for standardized DSM address directory management and synchronization workflows that support universal access in a timely manner.Our objective was to develop best practices for maintenance of DSM address directories and create recommendations to encourage adoption of DSM technology in the State of Texas.Texas Health Services Authority (THSA) formed a workgroup focused on increasing DSM adoption. Between August 2021 and March 2022, workgroup members used a modified Delphi process to create a directory management best practice policy and published it in May 2022. To measure the effect of the policy, THSA monitored volume of messages sent in a group of 38 hospitals before and after the workgroup was established.Organizations should standardize DSM address data and routinely sync with external databases to ensure seamless, vendor-independent message flow. Additionally, health systems are expected to update directory entries immediately upon any change in practitioner's status. Between September 2021 and December 2022, there was a decrease in Direct messages not sent due to no known address, from 50 to 42%, respectively. Additionally, between July 2021 and March 2024, organizations participating in the policy development reported a steady monthly increase of new Direct addresses issued.Health care organizations should adopt a consistent workflow for maintaining their DSM address directories and regularly synchronize with external databases to facilitate unobstructed flow of messages and data. The Maintenance of Provider Database Dictionary Policy developed by the THSA can serve as a model for nationwide implementation and optimization of DSM as an important interoperability standard.
Keywords: communication; data management; health information exchange